Trafficking and Syrian refugee smuggling: evidence from the Balkan Route - Mandic, Danilo (2017)
As of March 2016, 4.8 million Syrian refugees were scattered in two dozen countries by the civil war. Refugee smuggling has been a major catalyst of human trafficking in the Middle East and Europe migrant crises. Data on the extent to which smuggling devolved into trafficking in this refugee wave is, however, scarce. This article investigates how Syrian refugees interact with smugglers, shedding light on how human smuggling and human trafficking interrelated on the Balkan Route. I rely on original evidence from in-depth interviews (n = 123) and surveys (n = 100) with Syrian refugees in Jordan, Turkey, Greece, Serbia, and Germany; as well as ethnographic observations in thirty-five refugee camps or other sites in these countries. I argue that most smugglers functioned as guides, informants, and allies in understudied ways—thus refugee perceptions diverge dramatically from government policy assumptions. I conclude with a recommendation for a targeted advice policy that would acknowle